2017
DOI: 10.17509/mimbardik.v2i1.6019
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Planned Behaviour and Readiness for Changes: Implication for Organisations

Abstract: An organisation’s long term survival in today’s challenging environment will depend on constant adaptation to changes in the environment. The majority of behavioural theories acknowledged individual as the central focus. Certain environmental or situational factors and applicable change-related processes have been recognised and studied as having significant influence in determining individual, group, and organisational behaviours. In the context of readiness for change, the theory of planned behaviour would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Social marketing programs have been based on theoretical models/tools for promoting behavior change. The most commonly used models are the HBM (Rosenstock et al, 1988), the EPPM (Popova, 2012; Witte, 1992), the TRA (Fishbein & Ajzen, 1975), the SCM (DiClemente et al, 1985), and the EM (Glanz et al, 2009; Ogbodoakum & Abiddin, 2017). The HBM has been applied to a broad range of health behaviors, including health promotion (e.g., contraceptive use, diet, and exercise), illness or risk avoidance (e.g., smoking, child vaccination), compliance with recommended medical regimens, and use of clinical and medical services.…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%
“…Social marketing programs have been based on theoretical models/tools for promoting behavior change. The most commonly used models are the HBM (Rosenstock et al, 1988), the EPPM (Popova, 2012; Witte, 1992), the TRA (Fishbein & Ajzen, 1975), the SCM (DiClemente et al, 1985), and the EM (Glanz et al, 2009; Ogbodoakum & Abiddin, 2017). The HBM has been applied to a broad range of health behaviors, including health promotion (e.g., contraceptive use, diet, and exercise), illness or risk avoidance (e.g., smoking, child vaccination), compliance with recommended medical regimens, and use of clinical and medical services.…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%
“…Theory of Planned Behavior merupakan pengembangan dari Theory of Reasoned Action dengan tambahan konsep Perceived Behavior Control. Teori ini digunakan untuk meramalkan pertimbangan perilaku karena perilaku dapat dipertimbangkan dan direncanakan (Ogbodoakum & Abiddin, 2017). Theory of Planned Behavior memiliki keunggulan dibandingkan teori perilaku lainnya karena dapat mengidentifikasi keyakinan seseorang tentang pengendalian atas hasil perilaku, sehingga membedakan antara perilaku yang dikehendaki dan yang tidak dikehendaki (Ajzen, 1991).…”
Section: Tinjauan Pustakaunclassified
“…According to studies related to the change process (Saaid, 2016;Strebel, 1994;Waddell & Sohal, 1998), the effectiveness of any transformation is dependent on the employees' readiness to adopt and support the change process. Moreover, several scholars indicated that employee support is the primary antecedent to implementing an organizational change initiative successfully (Jimmieson et al, 2004;Peach et al, 2005;Ogbodoakum & Abiddin, 2017;Jimmieson et al, 2009) other studies determined that the failure or success of organizational changes depends on the employees' change-supportive behaviours or (readiness towards the change) (Kim et al, 2011;Rafferty et al, 2013).…”
Section: Introductionmentioning
confidence: 99%